Electromagnetic Fields and Waves : Fundamentals of Engineering - Riad, Sedki M.; Salama, Iman M. (McGraw-Hill Education, 2020)
This core introductory-level undergraduate textbook offers solid coverage of the fundamentals of electromagnetic fields and waves. Written by two electrical engineering experts and experienced educators, the book is designed to accommodate both one- and two-semester curricula. Electromagnetic Fields and Waves: Fundamentals of Engineering presents detailed explanations of the topic of EM fields in a holistic fashion that integrates the math and the physics of the material with students' realistic preparation in mind. You will learn about static and time-varying fields, wave propagation and polarization, transmission lines and waveguides, and more.